Generation of intense sub-two cycle pulses by nonlinear post compression of a high repetition rate Tm:fiber CPA - Gebhardt, Martin; Gaida, Christian; Heuermann, Tobias; Jauregui, Cesar; Antonio-Lopez, Jose; Schülzgen, Axel; Amezcua-Correa, Rodrigo; Limpert, Jens (Optics InfoBase Conference Papers, 2018)
We present nonlinear self-compression of ultrashort pulses from a powerful thulium-doped fiber laser using a gas-filled antiresonant hollow-core fiber. 104 µJ, sub-2 cycle pulses have been generated around 1.85 µm at 98 kHz repetition rate.
CRIS-Team Scopus Importer:2023-04-20